Perceptions of Healthcare Access for Patients with Soft Tissue Tumor Symptoms at Painan Hospital, West Sumatra - Adnan Andisyah Alfathin; Pinta Pudiyanti Siregar (UMSU, 2026)
Introduction: Access to healthcare services plays a crucial role in the management of patients with soft tissue tumor symptoms. Patients perceptions of healthcare accessibility may influence disease management, symptom severity, and prognosis. Easy access can facilitate early diagnosis and treatment, improve quality of life, and lead to better clinical outcomes, whereas limited access may delay care and worsen disease conditions. This study aimed to assess perceived access to healthcare services among patients with soft tissue tumor symptoms in a hospital in Painan, West Sumatra. Methods: A quantitative analytic observational study with a cross-sectional design was conducted among 33 patients presenting with soft tissue tumor symptoms. Data were collected using questionnaires to evaluate perceived healthcare access and symptom severity. Statistical analysis was performed using the Chi-square test. Results: Most participants were female, under 60 years of age, and belonged to a middle socioeconomic background. Severe symptoms were reported in 54.4% of patients, while 45.5% experienced mild symptoms. Lipoma was the most common tumor type (60.6%), with the posterior thorax being the most frequent tumor location (27.3%). The majority of respondents perceived healthcare access as easy (63.6%). A significant association was found between perceived healthcare access and symptom severity (p = 0.001), with easier access associated with milder symptoms. Conclusion: Perceived access to healthcare services is significantly associated with the severity of soft tissue tumor symptoms. Improving healthcare accessibility may contribute to earlier management and better clinical outcomes.